Analyisis Of The Covid-19 Pandemic Impact On The Aspects Of Contruction Work In The Task Force Project Of The Railway Enginering Agency Of East Java - Wawan Riyanta; Nurul Fitria Apriliani; Hana Wardani Puruhita (Litbang Pemas - Universitas Islam Lamongan, 2021)
The Covid-19 pandemic is a global pandemic that is currently sweeping the world with a significantly increased and sustainable spread globally. Adjustment of the way of life and strategy of each country in handling and preventing pandemics, especially health protocols and social restrictions certainly have a huge impact on all aspects of life. The construction sector as part of the economic actors also certainly felt the impact of the Covid-19 pandemic. This study analyzed the impact of the Covid-19 pandemic on construction project work with a case study of construction project work in the Working Unit of the Railway Engineering Agency (BTP) of East Java. The method used in this study uses factor analysis on aspects of construction work. From the analysis of data obtained the dominant affected variables on aspects of construction work are changing in project design, changes in organizational structure, changes in the volume of work, changes in the type of work and rescoping.